Etude préliminaire du régime alimentaire du Scomber japonicus (Houttuyn, 1782) pêché dans la région de Mostaganem. - FERRAOUN, HOUSSAM EDDINE (My University, 2022)
The diet of mackerel (Comber japonicas) was studied by analysis of the stomach contents of 35 individuals in the Mostaganem area. Stomach contents data analysis was done by the methods: Nm importance index, Q food index. The vacuity coefficient is 55%, trophic activity is influenced by the physiological state of the fishand environmental conditions. The food spectrum of mackerel is broad, and primarily primarily fish, polychaetes, crustaceans (copepods, amphipods), and cephalopods. Fish are in first position with a very high Q food coefficient, so they are primarily prey followed by polychaees, crustaceans (copepods, amphipods) and cephalopods, which are occasional prey. Mackerel shows a dual feeding strategy: the specialization strategy for fish and the generalization strategy for other prey.
Keywords: Scomber japonicus; diet; Mostaganem area; stomach contents